PENINGKATAN KAPASITAS PETERNAK MELALUI EDUKASI TEKNOLOGI PEMBUATAN SILASE RANSUM KOMPLIT DI PETERNAKAN SAPI NUSA FAUNA PADANG - Ferry Lismanto Syaiful; Fauzia Agustin; Benny Satria; Deni Novia (Jurnal Hilirisasi IPTEKS, 2025)
Complete A common challenge in smallholder beef cattle fattening enterprises is the fluctuation in the availability and quality of forage. Fermented feed technologies, such as complete ration silage, offer a promising solution for ensuring a sustainable supply of nutritious feed. This activity aimed to improve farmers’ knowledge and understanding of the techniques involved in producing high-quality complete ration silage for cattle feed at the Nusa Fauna Padang cattle farm. The programme was conducted at the Nusa Fauna Padang farm and involved lecturers and students from Andalas University, as well as local cattle farmers. The methods employed included preparatory stages, dissemination through participatory extension sessions, and an evaluation of the activity. Farmers were introduced to various feed ingredients such as rice straw, green forage, and molasses, as well as proper fermentation techniques to produce high-quality silage. The results showed a significant improvement in farmers’ knowledge and understanding regarding the production of complete ration silage. The utilization of this silage not only enhanced cattle productivity at the fattening farm but also reduced dependency on seasonal fresh forage and increased feed efficiency. As such, the complete ration silage technology presents a long-term solution for ensuring the availability of nutritious, stable, and durable feed. In conclusion, this educational activity successfully enhanced farmers’ capacity and opened up opportunities for the development of locally based feed technologies. It is recommended that such extension programmers be continued with follow-up assistance to ensure the effective implementation of silage production by farmers.